Analysis of Biomarker Levels in Nasopharyngeal Swabs, Serum, and Saliva Across Different Health Conditions - Mina Pencheva; Neshka Manchorova-Veleva; David Baruh; Georgi Rusinov; Lyubomir Vangelov (Life)
Background: Coronavirus disease 2019 (COVID-19) is associated with a wide variety of clinical manifestations. Aim: This study aims to evaluate the levels of angiotensin-converting enzyme 2 (ACE2), metalloprotease 17 (ADAM17), Interleukin-17A (IL-17A), transmembrane serine protease 2 (TMPRSS2), apelin (AP), and vitamin D (VD) biomarkers in nasopharyngeal swab (NPS), serum, and saliva, as well as the change in their values depending on the health status of individuals. Material and methods: The analysis was performed by using enzyme-linked immunosorbent assay (ELISA) methods. Results: Comparing the levels of the investigated markers in saliva, we found significantly elevated ACE2 values in vaccinated patients, followed by those with severe COVID-19, compared to healthy, previously infected, and mild COVID-19 groups. For TMPRSS2, IL-17A, ADAM-17, and AP, values were significantly higher in all non-healthy groups (previously infected, mild, and severe COVID-19) compared to healthy individuals. Serum levels of VD were consistently low across all five studied groups, suggesting values below normal ranges. Analysis of marker data in saliva, NPS, and serum revealed a positive correlation between NPS and serum and saliva and serum, as well as between saliva and NPS for all studied markers. Conclusions: In summary, monitoring changes in biomarkers present in Saliva holds promise as a predictive tool for various diseases. This approach enables the early implementation of preventive measures and protective strategies, potentially improving overall health outcomes.